Survey of postgraduate medical physics programmes in the Asia-Oceania region - Wong, Jeannie Hsiu Ding; Ng, Kwan Hoong; Sarasanandarajah, Sivananthan (Elsevier, 2019)
The increased use of medical imaging and radiation therapies has resulted in a high demand for medical physicists. Although medical physics programmes are well established in advanced countries, the same cannot be said for many low- and medium-income countries. In some countries, there may be huge variations in the graduates' skill and quality, which pose a problem in ensuring patient safety, providing quality assurance in treatments, optimisation of protocols and standardisation of quality. It also makes any yet-to-be-established regional peer recognition efforts problematic. In order to understand the depth of this problem, a survey was carried out as part of the home-based assignment under the RAS 6088 IAEA programme. A large diversity in terms of course content, duration, clinical training and student profile could be observed across the Asia-Oceania universities surveyed. Out of 25 programmes, only six received recognition from professional bodies, and they were mostly in Australia and New Zealand. Hence, to ensure quality education, a regional curriculum model needs to be developed to harmonise standards. And there is still a long way to go towards standardizing medical physics education and clinical training in the region. © 2019 Associazione Italiana di Fisica Medica